Defining excellence in simulation programs - Maxworthy, Juli C.; Epps, Chad A.; Okuda, Yasuharu; Mancini, Mary E.; Palaganas, Janice C.; Society for Simulation in Healthcare (Philadelphia : Wolters Kluwer, 2023)
"Official publication of the Society for Simulation in Healthcare. This text meets the needs of the increasing numbers of healthcare practitioners, researchers, and educators using simulation techniques for education, assessment, and research. Provides clear definitions and best practices for the many types of simulation programs. It adeptly covers all areas of program management, including staffing, funding, equipment, and education models. Definitive guide to designing, building, and implementing successful cost-effective research-based simulation programs"--
Simulation Standards -- Simulation Modalities -- Simulation Methods -- Management -- Funding -- Environmental Design -- Educational And Content Development -- Delivery Of Simulation -- Research -- Resources
Includes bibliographical references and index
Keywords: Nursing -- Study and teaching -- Simulation methods; Simulated patients; Patient Simulation; Education, Nursing -- methods; Competency-Based Education -- methods; Evidence-Based Nursing -- methods